Advanced Pointing Imaging Camera (APIC) for planetary science and mission opportunities. (December 2020) - Park, Ryan S.; Riedel, Joseph E.; Ermakov, Anton I.; Roa, Javier; Castillo-Rogez, Julie; Davies, Ashley G.; McEwen, Alfred S.; Watkins, Michael M.
Abstract: The Advanced Pointing Imaging Camera (APIC) is designed to obtain high-resolution imaging data to measure a target's geophysical and geodetic properties. The development of APIC originates from NASA's Homesteader program of technology development for candidate New Frontiers missions. The unique science enabled by APIC derives from its ability to simultaneously take images of the target and star field, allowing high-precision camera pointing knowledge with each high-resolution target image. APIC is small (28 ​cm ​× ​18 ​cm ​× ​24 ​cm encompassing volume), light-weight (6 ​kg total), and moderate in power (13 ​W maximum) while being high performance and robust to long missions in deep space. APIC incorporates two imagers, one narrow-angle camera (NAC) and one wide-angle camera (WAC) that can operate simultaneously. Both cameras utilize the CMOS-based Mars 2020 Engineering Camera technology with an option of either clear or Red-Green-Blue colors and have wide apertures to enable short exposures and thus perform at a wide range of targets. The NAC has a pixel resolution of 18 ​μrad and 4° field of view and the WAC has a pixel resolution of 82 ​μrad and 18° field of view. APIC also has two gimbals, allowing rapid camera pointing updates without the need to change the spacecraft attitude; thus, not interfering with other onboard sensors or spacecraft operations. Both gimbals are capable of compensating for relative spacecraft-target motion (i.e., image motion compensation) with an angular speed of up to 30°/s (i.e., 0.5 ​rad/s). Many of APIC components are commercial-off-the-shelf (COTS), or adapted from other NASA flight programs, which makes APIC very competitive in cost and gives it a high technical maturity. APIC's high-resolution images enable the determination of high-accuracy topography for geologic studies. This paper presents details of APIC's characteristics and functionalities as well as specific science objectives that APIC data can address, such as measuring a geometric tidal flexing through estimating the tidal Love number, h 2 and l 2, and small rotational effects, such as libration and precession, of natural satellites and small bodies (i.e., asteroids and comets) that are key to exploring a planetary body's interior. Improved knowledge of spacecraft orbit via landmark tracking using the APIC data would also improve the recovery of low-degree gravitational parameters such as k 2 . In this paper, the performance of APIC is presented by showing how well the tidal deformation and libration measurements can be recovered with realistic mission scenarios and configurations. Graphical abstract: Image 1 Highlights: The Advanced Pointing Imaging Camera (APIC) is designed to measure geophysical and geodetic properties of a target body. APIC's narrow-angle camera and wide-angle camera are mounted as an optical bench system and can slew simultaneously. APIC can simultaneously take the image of a target and the star field, allowing high-precision camera pointing for each target image. APIC is ideal for missions to body with strong tidal interactions by measuring h2 ​and l2, and for missions with high flyby speed. APIC ​can measure small rotational effects, such as libration and precession, and obtain high-resolution topography and albedo.